Corporate Social Responsibility in the agri-food sector: the case of GMOs - Heyder, Matthias; Theuvsen, Ludwig (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2010)
Genetically modified organisms (GMOs) are handled differently in different countries. Whereas global acreage of GMOs jumped to 134 million hectares in 2009 [Cultivation... 2010], in many European countries opposition to GMOs is still strong, and their acreage is very small. This situation poses a difficult situation for many companies and their corporate social responsibility [CSR] strategies. Against this background, we conducted an online survey of 170 agribusiness firms in order to shed some light on how companies handle the conflict between, on the one hand, the growing use of GMOs worldwide and, on the other, the rejection of GMOs by European consumers. The empirical results show that many agribusiness firms perceive the use of GMOs as a highly relevant management issue that shapes their CSR strategies. All in all, agribusiness firms apply a wide spectrum of CSR activities, furthermore, CSR is considered a top management responsibility. GMOs are of aboveaverage relevance in firms that have been criticized for their attitudes towards and use of GMOs. The empirical results have interesting implications for the management of CSR and legitimacy in the agribusiness sector